Studies on physiological aspects in Wheat and responses to Salinity Stress - Ritu Nandal; Seema Kumari (Innovative Research Thoughts, 2018)
A variety of physiological, biochemical, and molecular mechanisms have evolved to allow plant species to cope with salinity stress by modifying metabolic processes. Mechanisms may involve ion compartmentalization, ion transport and uptake, the synthesis of osmoprotectants, and antioxidant enzyme activation (Rathinasabapathy, 2000; Gupta and Huang, 2014). Using ion hemostats, plants can maintain ion balance within their cells, and this helps them cope with high Na+ and Cl- concentrations (Niu Xiaomu et al., 1995). Extreme ratios of Na+/Ca2+, Na+/K+, Ca2+/Mg2+, and Cl-/NO3 are formed, which in turn results in osmotic and specific ion injury (Alam, 1999; Grattana and Grieveb, 1999). Some plant species, however, have the capability of preserving tissue ion equilibrium. This mechanism primarily governs the movement of sodium inside plant cells.